Nilai-Nilai Lingkungan Dalam Tafsir Al-Misbah Menurut Perspektif Qurais Shihab - Andalan, Satrio; Admizal, Iril; Suriyadi, Suriyadi; Zakiar, Zakiar (Journal Peqguruang: Conference Series, 2024)
This study aims to identify and analyze environmental values in Tafsir Al-Misbah based on the perspective of Quraish Shihab. Tafsir Al-Misbah is one of the works of Qur'anic interpretation that is comprehensive and relevant in answering various contemporary issues, including environmental issues. Using a qualitative approach and content analysis method, this study explores verses related to environmental themes and how Quraish Shihab's interpretation provides a contextual view of human responsibility in protecting nature. The results of the study show that Quraish Shihab through Tafsir Al-Misbah emphasizes the importance of moderation, moral responsibility, and balance in human interaction with the environment. Values such as nature conservation, resource sustainability, and prohibition of overexploitation are elaborated in depth in this interpretation. This research is expected to contribute to developing environmental awareness based on religious values, as well as supporting environmental conservation efforts that are in line with the principles of Islamic teachings.